Multipurpose tree selection for silvopastoral systems on acid Ultisols. The effect of grass competition on early growth of tree and shrub species - Larbi, Asamoah; Ladipo, D.O.; Adekunle, I.O.; Smith, Jimmy W.; Jabbar, M.A. (Informa UK Limited, 1998)
An experiment was conducted on an Ultisol at the International Institute of Tropical Agriculture (IITA) High Rainfall Station, Onne, in the humid forest zone of south-eastern Nigeria. The objective of the study was to define groups of multipurpose trees using multiple variables to select materials for detailed tree-grass or agro-silvopastoral studies. Survival and early growth of 15 multipurpose tree and shrub species (MPTs) when grown alone or in association with Brachiaria mutica or Panicum maximum were evaluated 12 mo after grass establishment. Grass competition significantly reduced seedling survival, height and diameter growth, including number of branches. Above- and below-ground phytomass were also reduced and there was increased stem and crown damage by insect pests in most MPTs. The effect of the competitive stress differed between grass species and among MPTs, suggesting that different competitive mechanisms were involved between grass species and MPTs. Based on means of all variables, Dactyladenia barteri, Albizia niopoides, A. lebbeck, Bauhinia monandra. Flemingia macrophylla and I. edulis appeared to offer considerable prospects as companion MPTs in swards of brachiaria and panicum. Results indicated that competition from cultivated grass could influence early growth of MPTs on acid soils.